Limited Neutralization of Authentic Severe Acute Respiratory Syndrome Coronavirus 2 Variants Carrying E484K In Vitro. (5th June 2021) - Widera, Marek; Wilhelm, Alexander; Hoehl, Sebastian; Pallas, Christiane; Kohmer, Niko; Wolf, Timo; Rabenau, Holger F; Corman, Victor M; Drosten, Christian; Vehreschild, Maria J G T; Goetsch, Udo; Gottschalk, Rene; et al.
Abstract: Whether monoclonal antibodies are able to neutralize severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern has been investigated using pseudoviruses. In this study we show that bamlanivimab, casirivimab, and imdevimab efficiently neutralize authentic SARS-CoV-2, including variant B.1.1.7 (alpha), but variants B.1.351 (beta) and P.2 (zeta) were resistant against bamlanivimab and partially resistant to casirivimab. Whether antibodies are able to neutralize severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variantshas been investigated using pseudoviruses. We show that authentic SARS-CoV-2 carrying E484K were resistant against bamlanivimab and less susceptible to casirivimab, convalescent and vaccine-elicited sera. Abstract : Authentic severe acute respiratory syndrome coronavirus 2 B0.1.1.7 (alpha) is efficiently neutralized by monoclonal antibodies and convalescent and vaccine-elicited serum samples. However, bamlanivimab, casirivimab, convalescent, and BNT2b2 or messenger RNA1273 vaccine-elicited serum samples are less effective against authentic B0.1.351 (beta) and P0.2 (zeta), both carrying E484K in vitro.